Analisis Penanganan Kompensasi Keterlambatan Penerbangan ( Delay ) Terhadap Penumpang Di Bandar Udara Internasional Sultan Aji Muhammad Sulaiman Sepinggan – Balikpapan - Muhammad Tunjung Rohmatullah; Ubaedillah Ubaedillah; Rini Sadiatmi (Asosiasi Riset Ilmu Teknik Indonesia, 2025)
This study aims to analyze the implementation of compensation for flight delays at Sultan Aji Muhammad Sulaiman Sepinggan International Airport, Balikpapan. This study uses a qualitative descriptive approach, with data collection techniques through direct observation, in-depth interviews with airline staff, and documentation during On the Job Training (OJT) activities. The main focus of the study is to evaluate the extent to which passenger rights have been fulfilled by airlines in accordance with applicable regulations, specifically the Regulation of the Minister of Transportation of the Republic of Indonesia Number PM 89 of 2015 concerning Handling Flight Delays. The results of the study indicate that the implementation of compensation by several airlines is still not optimal. There are discrepancies between regulatory provisions and implementation in the field, such as late delivery of information, disproportionate compensation, and uneven service among airlines. Passengers often do not receive clarity regarding their rights, and complaint mechanisms are still limited. Factors causing delays include technical problems, bad weather, inefficient operational management, and limited number and capacity of human resources on duty. This study emphasizes the need to improve the internal and external communication systems of airlines so that information related to delays and compensation can be conveyed transparently and in a timely manner. In addition, airlines need to conduct regular evaluations of standard operating procedures (SOPs), strengthen customer service training for staff, and foster synergy between work units to improve responsiveness to unforeseen situations. Regulators and airport authorities need stricter oversight and the implementation of strict administrative sanctions for violations of passenger rights. These findings provide important contributions to the formulation of public policy in the air transportation sector and provide input for improving services that are more humane, accountable, and oriented toward customer satisfaction.